Leverage interactions: a national accounts approach - Celestino Giron; Marta Rodríguez-Vives (European Central Bank (ECB), 2017)
The policy focus on excessive leverage in the euro area has raised interest in developing comprehensive analytical approaches to better understand the interrelationship between leverage and deleveraging processes across economic agents. In particular, the interplay between government debt and private leverage is attracting increasing attention in the current context of simultaneous deleveraging adjustments. However, analyses of the subject are generally partial in that they fail to take into account feedback effects on balance sheet positions across economic agents. This paper attempts to clarify these cross-agent interlinkages by examining concepts, relationships and restrictions taken from the national accounts framework. Hence, the paper presents a mechanism that captures how increased leverage in certain agents contributes, ceteris paribus, to a reduction in leverage in the rest of the economy. The novelty of the underlying framework for leverage behaviour is that it takes the financial assets held by agents into consideration.
Keywords: E01; E62; H3; H6; 330; balance sheet approach; indebtedness; leverage; national accounts